2013
DOI: 10.1177/1533317513495107
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Galectin-3 Levels in the Serum of Patients With Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder of the central nervous system. Galectin-3 (Gal-3) is characterized by a conserved sequence within the carbohydrate recognition domain. The effect of Gal-3 in AD is presently unknown. In this study, we found significantly increased Gal-3 serum levels in patients with AD compared to control participants (P=.017). There was no significant difference between patients with mild cognitive impairment (MCI) and healthy controls (P=.143) or between patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 35 publications
6
62
0
1
Order By: Relevance
“…These results are consistent with reports that integrin and integrin-associated protein facilitate LTP and memory performance in rats (Staubli et al, 1990; Huang et al, 1998). They are also congruent with the finding that galectin-3 levels are increased in the serum of Alzheimer’s disease patients (Wang et al, 2015). Further support comes from the observations that a lack of galectin-3 facilitates motor function recovery after spinal cord injury (Mostacada et al, 2015), and that galectin-3 contributes to hypoxic-ischemia injury and ischemia-induced neuronal death (Doverhag et al, 2010; Satoh et al, 2011), findings that suggest a role for galectin-3 in negative regulation of neuronal plasticity.…”
Section: Discussionsupporting
confidence: 89%
“…These results are consistent with reports that integrin and integrin-associated protein facilitate LTP and memory performance in rats (Staubli et al, 1990; Huang et al, 1998). They are also congruent with the finding that galectin-3 levels are increased in the serum of Alzheimer’s disease patients (Wang et al, 2015). Further support comes from the observations that a lack of galectin-3 facilitates motor function recovery after spinal cord injury (Mostacada et al, 2015), and that galectin-3 contributes to hypoxic-ischemia injury and ischemia-induced neuronal death (Doverhag et al, 2010; Satoh et al, 2011), findings that suggest a role for galectin-3 in negative regulation of neuronal plasticity.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly we recently reported that LPS increases the expression of galectins within the mouse brain (Brooks et al, 2016a). The galectins are a group of lectins that have been implicated in several central diseases and neurological disorders (John and Mishra, 2016; Liu and Rabinovich, 2010; Lutomski et al, 1997; Stancic et al, 2011; Wang et al, 2015b). Like, corticosteroids, Gal-9 interacted with IFNγ to accentuate Ido1-FL expression (Brooks et al, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of serum Gal-3 is not limited to cancer as it has been associated with other diseases such as systemic lupus erythematosus, rheumatoid arthritis, Alzheimer's disease and Behçet's disease (15-17). Circulating Gal-3 was positively associated with the type 2 diabetes, which could be reduced by anti-diabetes metformin (19).…”
Section: Introductionmentioning
confidence: 99%